EEG FREQUENCIES PATTERN AS BRAIN SIGNATURE OF EMOTIONAL BURNOUT. ANXIETY TENSION STAGE FORMATION - Semen A. Mushta; Svitlana P. Palamar; Dmytro V. Harmatiuk; Anton O. Popov; Joao M. Alves Ferreira; Mykola Yu. Makarchuk; Sergii V. Tukaiev (Клінічна та профілактична медицина)
Introduction. The prospect of increasing annually makes burnout a global phenomenon, one of the most common stress-related and mental disorders. Emotional burnout leads to serious destructive consequences for society, organizations, and interpersonal relationships due to mental and behavioural changes. Burnout develops gradually and often goes unnoticed, with symptoms that may take years to manifest and lead to significant mental and behavioral changes. Despite its impact, the processes underlying burnout remain largely unknown due to a lack of specialized studies identifying specific biomarkers. Early detection of burnout, particularly at the critical onset of symptoms, is essential.